PRINCIPAL SUPERVISION IN INCREASING ELEMENTARY SCHOOL TEACHER’S PERFORMANCE - Sumarni; Rosleny Babo; Muhlis Madani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
School quality is related to the supervision of the principal. Principal supervision is an effort to improve teaching and learning process or assistance to teachers in order to help students to be better in learning. This study aims to describe the supervision of principals in improving the performance of teachers in SDN Center Mawang, Bontomarannu District, Gowa Regency, South Sulawesi. This research was a qualitative research with a case study approach using observation method by looking at the activities in schools, interviews to find out the implementation of supervision in schools and documentation by looking at the results of supervision of principals or teacher performance assessment. The results of the study showed that the principal supervision, monitoring and assessment had not yet been implemented and still needed to be evaluated. The inhibiting factors of the principal supervision were internal and external obstacles.